Rejection of submitted quotation under issued letter reference no BRACU-NCP.2019.89A - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the rejection of submitted quotation under issued letter reference no BRACU-NCP.2019.89A of BRACU new campus project site.